PC.106 Cerebral Injury and Early Childhood Neurodevelopmental Outcome following Neonatal Encephalopathy in a Middle-income Country. (9th June 2014) - Pauliah, SS; Lally, PJ; Price, DL; Bainbridge, A; Kurien, J; Sivaswami, N; Cowan, FM; Balraj, G; Swamy, R; Madhavan, V; Nair, M; Krishnakumar, P; et al.
Abstract : Background: Although neonatal encephalopathy (NE), accounts for 1 million neonatal deaths annually in low-and middle-income countries (LMIC), underlying brain injury and long term outcomes are not well characterised in LMIC. Objective: To examine cerebral injury (using magnetic resonance (MR) biomarkers), and early childhood outcomes after NE in a government hospital in India. Design/Methods: We recruited 54 newborns (>36 wk and >1.8 kg) with NE (Thompson score ≥6) at age <6h, admitted to the neonatal unit at Calicut Medical College, India over 6 months. Conventional MRI (1.5T, Siemens Avanto), diffusion tensor MR imaging and thalamic proton MR spectroscopy (MRS) were performed aged <3 wk. Cerebral injury was graded and group-wise differences in white matter (WM) fractional anisotropy (FA) were examined using tract-based spatial statistics (TBSS). In survivors, adverse neurodevelopmental outcome at mean (SD) 3.4(0.2) years was defined as Bayley-III composite cognitive/motor score ≤85, slow head growth or cerebral palsy. Results: MR data available from 44 cases showed evidence of acute perinatal injury. WM changes were seen in 40(91%), basal ganglia/thalamic (BGT) injury in 12(27%). Six infants died neonataly, 16(42%) and had adverse neurodevelopmental outcome. TBSS showed a reduction in FA with adverse neurological outcomes, and in those who had moderate/severe BGT or cortical injury. Conclusions: Cerebral injury in this cohort appears to be of perinatal origin and may be amenable to treatment. Although NE stage and injury pattern was mild in the majority of infants, adverse outcomes were seen in 42% at 3½ years. Reduced WM FA was associated with adverse neurodevelopmental outcomes.